Detection of Viable Myocardium in Patients with Myocardial Infarction (MI) with Dobutamine Stress Echocardiography (DSE) Comparing with Single Photon Emission Computed Tomography (SPECT-MPI) - Azam, MG; Ahmed, N; Banerjee, Sajal Krishna; Ahmed, Chowdhury Meshkat; Rahman, Fazlur; Rahman, Md Mukhlesur; Mahmood, Manzoor; F, Rabin; Arefin, Minhaz; Karim, Md Mahmudul (University Heart Journal, 2022)
Aims and objectives: To evaluate the role of Dobutamine Stress Echocardiography (DSE) in detecting viable myocardium in patients with myocardial infarction comparing with Single Photon Emission Computed Tomography (SPECT-MPI). Methodology: It was a prospective study, conducted over sixty one patients of MI in Bangabondhu SK Mujib Medical University (BSMMU). Serial DSE, SPECT-MPI and CAG were done and compared. Result: With DSE viable myocardium was found in 71.1% of territory supplied by LAD, 58.3% of territory supplied by LCX and 65.9% of territory supplied by RCA. With SPECT-MPI viable myocardium was found in 68.2% of territory supplied by LAD, 66.7% of territory supplied by LCX and 65.1% of territory supplied by RCA. Comparing two methods there was no significant difference between DSE and SPECT-MPI in determining viable myocardium (p>0.05). Conclusion: DSE is effective in detecting viable myocardium in patients with MI, which is comparable to SPECT-MPI. University Heart Journal 2022; 18(2): 98-100